Dataset of Denmark Strait Mooring Array 2014/15 - Moritz, Martin; Jochumsen, Kerstin; North, Ryan Peter; Valdimarsson, Heddin (Zenodo, 2019)
Data from Denmark Strait mooring array 2014/15 as used and described in Moritz et al. 2019: "Mesoscale Eddies observed at the Denmark Strait Sill" (submitted to JGR Oceans May 2019). The mooring array deployed in 2014/15 consisted of five current meters labeled DS1, DS20, DS2, DS21, DS22. DS1 and DS2 are the long-term moorings maintained by the Marine and Freshwater Research Institute (MFRI), Reykjavik, Iceland, and the University of Hamburg, Hamburg, Germany, respectively. Both consist of an upward-looking ADCP mounted within a floatation body, additionally equipped with a SeaBird MicroCAT SBE 37 below the ADCP, providing temperature and salinity information. For the experiment in 2014/15 DS20 had the same design and was positioned between DS1 and DS2. Further west, an ADCP and a MicroCAT were deployed as DS21 in a bottom mounted trawl proof frame. Mooring DS22 had an Aanderaa RCM8 and a MicroCAT and completed the array on the Greenlandic shelf. From the ADCPs we obtained vertical velocity profiles spanning 400 m. The RCM performed single-point measurements at a height of 22 m above the bottom. The five moorings were separated by 5 to 10 km, thus spanning approximately 30 km from the deepest point of the passage towards the Greenlandic shelf. The temporal resolution of our data set is hourly and covers 300 days. The data were processed, quality controlled and corrected. The correction of the data took into account a low velocity bias that affected the measurements of the Long Ranger ADCPs. The coordinate system was rotated such that the v-component is oriented along the mean flow direction and the u-component across the mean flow. Positive v is upstream (northeastward) and negative v is directed downstream (southwestward). Positive u is towards Iceland (southeastward) and negative u is directed towards Greenland (northwestward). The data are provided in MATLAB format: --- array_2014_15_meta.mat: moor_name: Mooring name moor_lat: Latitude of mooring position [°N] moor_lon: Longitude of mooring position [°E] ...